9(x+8)-6(x-3)+14=5(x-3)+11

Simple and best practice solution for 9(x+8)-6(x-3)+14=5(x-3)+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(x+8)-6(x-3)+14=5(x-3)+11 equation:


Simplifying
9(x + 8) + -6(x + -3) + 14 = 5(x + -3) + 11

Reorder the terms:
9(8 + x) + -6(x + -3) + 14 = 5(x + -3) + 11
(8 * 9 + x * 9) + -6(x + -3) + 14 = 5(x + -3) + 11
(72 + 9x) + -6(x + -3) + 14 = 5(x + -3) + 11

Reorder the terms:
72 + 9x + -6(-3 + x) + 14 = 5(x + -3) + 11
72 + 9x + (-3 * -6 + x * -6) + 14 = 5(x + -3) + 11
72 + 9x + (18 + -6x) + 14 = 5(x + -3) + 11

Reorder the terms:
72 + 18 + 14 + 9x + -6x = 5(x + -3) + 11

Combine like terms: 72 + 18 = 90
90 + 14 + 9x + -6x = 5(x + -3) + 11

Combine like terms: 90 + 14 = 104
104 + 9x + -6x = 5(x + -3) + 11

Combine like terms: 9x + -6x = 3x
104 + 3x = 5(x + -3) + 11

Reorder the terms:
104 + 3x = 5(-3 + x) + 11
104 + 3x = (-3 * 5 + x * 5) + 11
104 + 3x = (-15 + 5x) + 11

Reorder the terms:
104 + 3x = -15 + 11 + 5x

Combine like terms: -15 + 11 = -4
104 + 3x = -4 + 5x

Solving
104 + 3x = -4 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
104 + 3x + -5x = -4 + 5x + -5x

Combine like terms: 3x + -5x = -2x
104 + -2x = -4 + 5x + -5x

Combine like terms: 5x + -5x = 0
104 + -2x = -4 + 0
104 + -2x = -4

Add '-104' to each side of the equation.
104 + -104 + -2x = -4 + -104

Combine like terms: 104 + -104 = 0
0 + -2x = -4 + -104
-2x = -4 + -104

Combine like terms: -4 + -104 = -108
-2x = -108

Divide each side by '-2'.
x = 54

Simplifying
x = 54

See similar equations:

| -3.5n=2.51 | | B^2+8b=64 | | 3x^2+60=24x | | .80x+x=162 | | g(x)=-x^3+2x^2+11x-12 | | 3.2+0.3x=0.2+1.14 | | x-(58)=65 | | 3n+4(-4+1)=2n+4 | | f(x)=x^2+6x+11 | | 5b-4b=6.2b | | 4x^2+4x=-5 | | 68=x+x^2 | | -3(t-5)-11= | | (3x-8)(4-x)=0 | | 12p=9+14+p | | v/615 | | y=4.5x+2.5 | | 4.8/3.6 | | 9x-7=9x-7 | | X(4)+x(2)=86 | | 0.5-1.1=4.9 | | 9-1+3y=4+y-2(3-2y) | | 0.80x+20.00=100.00 | | (2r+3)(2r-1)=-3(r+1) | | (4g-1)(6g-1)=0 | | (d+3)(9d-2)=0 | | 9x+29=4 | | 11/x=x/11 | | -5(t-2)-7= | | 42=2y-10 | | 10*1/3= | | 8y^2+8y+7=0 |

Equations solver categories